Age structure of population in the city of Maribor in the years between 1981 and 2002 - Horvat, Uroš (Journal for Geography, 2007)
The article discusses the characteristics of age structure of population in the city of Maribor (Slovenia) between 1981 and 2002. The development basically followed the tendencies in other larger Slovene cities. However, the process of aging of population is most intensive in Maribor. Maribor has, compared to other larger cities, the highest percentage of elderly population and the highest aging index. Due to the influence of various social and economic factors, the demographic circumstances differ from one part of the city to another. Analyze in 38 parts of the town shows the significant correlation between the demographic development, the development of function and period of construction of individual parts of the town.